Histone H4 deacetylation plays a critical role in early gene silencing during neuronal apoptosis - Schlamp Cassandra L (BMC Neuroscience, 2010)
Abstract Background Silencing of normal gene expression occurs early in the apoptosis of neurons, well before the cell is committed to the death pathway, and has been extensively characterized in injured retinal ganglion cells. The causative mechanism of this widespread change in gene expression is unknown. We investigated whether an epigenetic change in active chromatin, specifically histone H4 deacetylation, was an underlying mechanism of gene silencing in apoptotic retinal ganglion cells (RGCs) following an acute injury to the optic nerve. Results Histone deacetylase 3 (HDAC3) translocates to the nuclei of dying cells shortly after lesion of the optic nerve and is associated with an increase in nuclear HDAC activity and widespread histone deacetylation. H4 in promoters of representative genes was rapidly and indiscriminately deacetylated, regardless of the gene examined. As apoptosis progressed, H4 of silenced genes remained deacetylated, while H4 of newly activated genes regained, or even increased, its acetylated state. Inhibition of retinal HDAC activity with trichostatin A (TSA) was able to both preserve the expression of a representative RGC-specific gene and attenuate cell loss in response to optic nerve damage. Conclusions These data indicate that histone deacetylation plays a central role in transcriptional dysregulation in dying RGCs. The data also suggests that HDAC3, in particular, may feature heavily in apoptotic gene silencing.